Formation of low-T hydrated silicates in modern microbialites from Mexico and implications for microbial fossilization - Zeyen, Nina; Benzerara, Karim; Li, Jinhua; Groleau, Alexis; Balan, Etienne; Robert, Jean-Louis; Estève, Imène; Tavera, Rosaluz; Moreira, David; López-García, Purificación (Frontiers in Earth Science, 2015)
Microbialites are organo-sedimentary rocks found in abundance throughout the geological record back to ~3.5 Ga. Interpretations of the biological and environmental conditions under which they formed rely on comparisons with modern microbialites. Therefore, a better characterization of diverse modern microbialites is crucial to improve such interpretations. Here, we studied modern microbialites from three Mexican alkaline crater lakes: Quechulac, La Preciosa and Atexcac. The geochemical analyses of water solutions showed that they were supersaturated to varying extents with several mineral phases, including aragonite, calcite, hydromagnesite, as well as hydrated Mg-silicates. Consistently, X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) analyses revealed that microbialites are composed of a diversity of mineral phases including aragonite and sometimes calcite, hydromagnesite, and more interestingly, a poorly-crystalline hydrated silicate phase. Coupling of scanning electron microscopy (SEM) with energy dispersive X-ray spectrometry microanalyses on polished sections showed that this latter phase is abundant, authigenic, magnesium-rich and sometimes associated with iron and manganese. This mineral phase is similar to kerolite, a hydrated poorly crystalline talc-like phase (Mg3Si4O10(OH)2·nH2O). Diverse microfossils were permineralized by this silicate phase. Some of them were imaged in 3D by FIB-tomography showing that their morphology was exquisitely preserved down to the few nm-scale. The structural and chemical features of these fossils were further studied using a combination of transmission electron microscopy and scanning transmission X-ray microscopy (STXM) at the carbon and magnesium K-edges and iron L2,3-edges. These results showed that organic carbon is pervasively associated with kerolite. Overall, it is suggested that the poorly-crystalline hydrated magnesium-rich silicate forms in many alkaline lakes and has a strong potential for fossilization of microbes and organic matter. Moreover, the frequent occurrence of such an authigenic silicate phase in modern lacustrine microbialites calls for a reappraisal of its potential presence in ancient rocks.